Fishery, reproductive biology and stock status of the Indian mackerel Rastrelliger kanagurta (Cuvier, 1817), landed along the north-east coast of India - Ghosh, Shubhadeep; Hanumantha Rao, M. V.; Mahesh, V. U.; Satish Kumar, M.; Rohit, Prathibha (Indian Journal of Fisheries, 2016)
The fishery, biology and stock status of Indian mackerel, Rastrelliger kanagurta (Cuvier, 1817), landed along the north-east coast was studied during 2011-2014. The average annual catch was 52,206 t. Catch was more or less equally contributed by trawlers, gillnetters and seiners with average catch rates of 3.05 kg h-1, 22.74 kg unit-1 and 140.09 kg unit-1 respectively. Catch was positively influenced by wind speed and negatively by sea surface temperature and precipitation. Growth in males was isometric, while it was allometric in females and indeterminates. Females outnumbered males in the commercial catches. Length at first maturity varied between 18.32 and 18.86 cm. Peak spawning season was during July - October and February - April. Relative fecundity was 567.51 ova per gram body weight. von Bertalanffy growth equation obtained was: Lt = 27.72 [1-e -1.2 (t + 0.023)]. Length at first capture and life span estimated were 12.78 cm and 2.48 years respectively. Natural mortality, fishing mortality and total mortality were 2.06, 3.69 and 5.75, respectively with an exploitation rate of 0.64. Peak recruitment was found to be during September-October. Maximum sustainable yield and yield per recruit were 40,675 t and 14.74 g respectively which were obtained by increasing the present fishing effort by 20%, but at the increased fishing effort, the increase in yield was a meager 0.53%, which indicates that the present level of fishing can be continued.